Mark I Role Model and Inspiring Catalyst : Some Characteristics from a Perspective of Four Decades - Nash, Peter (Cahiers de géographie du Québec, 1986)
Raoul Blanchard's impact on geographic thought in Canada can be summarized in five major categories: 1) a methodical seeder of geographic ideas during regular visits in a land which he loved ; 2) a provider of a tangible methodology to colleagues and students in Québec ; 3) a regionalist who transplanted the approach acquired from his mentor and fused it with his own individual synthesizing technique; 4) a networker who possessed a remarkable personal style of communication; and 5) a philosopher malgré lui who embraced and intertwined a number of epistemologies and stated that he rejected them all. Blanchard's three thousand plus pages on Canada constitute a scholarly, reliable, and readable base for first generation Canadian (Mark I) francophone geography. He was an inspiring catalyst and personal friend of the author and many of his contemporaries, and more importantly a Promethean progenitor to second and third generation Canadian geographers.